Community Composition and Distribution Pattern of Herbaceous Flora in Holi Area of District Chamba in Himachal Pradesh - Thakur, Kehar Singh; Kumar, Munesh; Bawa, Rajan; Kumari, Anita; Sharma, Anurag (International Journal of Economic Plants, 2020)
The present study was carried out in Holi Forest Range of district Chamba, which is the north-west district of Himachal Pradesh and is located between latitude 32o17’412’’ to 32o26’541’’N and longitude 76o31’504’’ to 76o35’385’’E. The territory is completely mountainous with altitude varying from about 2,000 feet (610 m) to about 21,000 feet (6,400 m) above the mean sea level. The quantitative information of herbs was collected from different sites i.e., Deol, Kut, Dal, Lahaud Dhar. Frequency (%), Density (plants m-2), Basal Area (cm2), Importance Value Index (IVI) and A/F ratio of plant species at different sites were recorded. Poa alpina was found to have highest frequency (90%) closely followed by Jurinea dolomiaea (80%) and Biebersteinia odora has the lowest frequency of 10%. Poa alpina has the highest density (60.6 plants m-2) at Dal followed by Gentiana kurrooa (35.8 plants m-2). Moschela esculenta was found to have highest basal area (1.234 cm2) at Kut. Viola serpens was the dominant species with highest value of IVI (78.77) closely followed by Poa alpina (65.91), Gentiana kurrooa (65.37) and Jurinea dolomiaea (65.36). Most of the species were distributed randomly followed by contagious pattern of distribution and least species were reported for regular distribution pattern.